Magnetic field generation using single-plate targets driven by kJ-ns class laser. (6th November 2020) - Kumar, Deepak; Singh, Sushil; Ahmed, Hamad; Dudžák, Roman; Dostál, Jan; Chodukowski, Tomasz; Giuffrida, Lorenzo; Hadjisolomu, Prokopis; Hodge, Thomas; Juha, Libor; Krouský, Eduard; Krůs, Miroslav; et al.
Abstract: Strong magnetic fields of upto 20 T, corresponding to a current of tens of kA were produced in a coil connected to a single-plate of cm 2 area irradiated by a kJ-ns laser pulse. The use of such macroscopic plates protects the coil from plasma debris, while maintaining a strong magnetic field for a time-scale much longer than the laser pulse duration. By correlating the measured magnetic field in the coil to the number of electrons emitted from the interaction zone, we deduce that the target capacitance is enhanced by two orders of magnitude because of the plasma sheath in the proximity of the focal spot. The particle-in-cell simulation illustrates the dynamics of sheath potential and current flow through the coil to ground, thus closing the circuit due to the escape of laser-produced hot electrons from the target.